Pengelolaan Bisnis Secara Administratif pada Omah Teh Nganjuk - Pramesti Intan Destari; Lia Nirawati (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Business is a collection of activities carried out by a person or group of people to produce products/services using certain methods and strategies to create product/service value that is different from competitors and seek profits to improve the welfare of the owner, employees and company. sustainable business development. Every business activity is of course always influenced by the dynamics that occur in the business environment. The business environment has a very large role in business success. The aim of this research is to understand business management administration and the development of the Nganjuk tea shop business. This research is qualitative research using a descriptive approach and data collection techniques used through observation, interviews and documentation. The research results show that Omah Teh Nganjuk implements administrative business management, namely by forming 3 teams which include a finance team, a product packaging team and a ready-to-eat team. With the formation of several teams, it is hoped that the administrative management of the Nganjuk tea house will be more focused, so that work can be completed more quickly and the business can run according to the initial plans that have been set. By managing the business administratively, the development of product marketing from Omah Teh Nganjuk is growing rapidly. Marketing is not only carried out in Nganjuk Regency, but has spread outside Nganjuk and even overseas. Marketing of Nganjuk tea products is carried out online and offline. Online marketing is carried out through social media (Instagram, TikTok, Facebook and Bakul Nganjuk market). Meanwhile, offline marketing is carried out in gift shops, orange shops, environmentally friendly shops, and at stands at events. With this online marketing, the Nganjuk tea shop can certainly expand its target market.